A Study of Causes Influencing a Reduction in the Number of Students Taking the Entrance Examination and Low Enrollment in Higher Education : https://doi.org/10.69692/SUJMRD090138 - Keoboualaphet, Soulideth; Choumo, Yelee; Phommaseng, Sisouri; SAN, Somephet; Seuangkinkeo, Amphanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purposes of this research were to: 1) examine the causes of a reduction in the number of students taking the entrance examination and low enrollment in Souphanouvong University, 2) examine the causes influencing a reduction in the number of students taking the entrance examination and low enrollment in Souphanouvong University, and 3) analyze the correlation between the causes and a reduction in the number of students taking the entrance examination and low enrollment in Souphanouvong University. A questionnaire was distributed to 750 students at high schools and technical vocational colleges and an in-depth interview was conducted with 15 respondents from the Department of Education and Sports in the northern provinces of Lao PDR. The data was analyzed by using contents analysis and SPSS Program version 25 to test the results of frequency, percentage, mean, standard deviation, Pearson correlation coefficient, and multiple regression analysis. The result revealed that reduction in the number of students taking the entrance examination at Souphanouvong University was at a medium level. It could be seen that the traveling, accommodation and related cost during the entrance examination were expensive, and the choice of choosing to study at another place were at a high level. The low enrollment of students at Souphanouvong University was at a medium level since the quota did not match with the demand of students, and some of them couldn’t afford the tuition fees which were at a high level. The cause influencing a reduction in the number of students taking the entrance examination and low enrollment in Souphanouvong University was at a medium level. It can be seen that the social and economic aspects are the key influencing factors at a high level, while the causes from university, family, choosing technical or vocational college and the students themselves were at a medium level. There are four causes correlated to a reduction in the number of students taking the entrance examination at Souphanouvong University, including university, economics, choosing to enroll in a technical vocational college, and the student themselves. On the other hand, there are five causes correlated to the low enrollment of students in Souphanouvong University, namely the causes of society, family, university, personal student, and economics. The result showed several causes that influence a reduction in the number of students taking the entrance examination and low enrolment at Souphanouvong University, which is an important evidence to develop strategies plans, consistent policies, implementation plans, and solutions to solve these causes more effectively.